Aplicabilidade de arame ultrafino na soldagem MIG / MAG de chapas de finas - Martins, Rúbia Zaidan (2018)
Given the variety of wire diameters available on the market today for use in the MIG/MAG process, the need for a better understanding of the influence of this parameter on the final welding result arises. The search for processes that provide better gains in productivity, rate of deposition, fusion and reduction of spatter, makes the discussion of parameters and consumables extremely important during the choice of the welding process to be used. In this way, it was proposed to evaluate the applicability of thin wire (Ø 0.6 mm) in relation to the Ø 1.0 mm wire, in MIG / MAG welding of 3 mm thick carbon steel plates in top joints (with and without opening), in three different positions: flat, vertical descending and overhead, through manual welding (semi-automatic process). In order to carry out the tests, an experimental procedure was developed that allowed the preliminary tests to find the best parameters to be used in the process, to be carried out in a workshop on a shop floor, simulating a real scenario of applicability. In the second stage of the tests carried out in Laprosolda, the objective was to draw a comparison between procedures (welding with 0.6 mm and 0.8 mm wire), through the use of a continuous flow water calorimeter and data acquisition system, maintaining the same methodology used in the preliminary stage. In all, approximately fifty tests were performed, using the thin wire of Ø 0.6 mm and the conventional wire of Ø 1.0 mm. In general, the obtained results allowed to observe that the wire of Ø 1,0 mm applied in the welding by short circuit, has better rate of deposition, fusion and greater thermal input, when compared to the wire of Ø 0,6 mm in the mode of spray transfer, making it more advantageous in different aspects.